第 12 类 RD Sharma 解 - 第 19 章不定积分 - 练习 19.25 |设置 3
计算以下积分:
问题 41. ∫cos -1 ((1 – x 2 )/(1 + x 2 ))dx
解决方案:
Given that, I = ∫cos-1((1 – x2)/(1 + x2))dx)
Let us considered x = tant
dx = sec²tdt
I = ∫cos-1((1 – tan2t)/(1 + tan2t)) sec2tdt
= ∫cos-1(cos2t)sec2tdt
= ∫2tsec2tdt
Using integration by parts,
∫u v dx = v∫ u dx – ∫{d/dx(v) × ∫u dx}dx + c
We get
I = 2[t∫sce2tdt – ∫(1∫sec2tdt)dt]
= 2[t × tan2t – ∫tantdt]
= 2[t × tan2t – logsect] + c
= 2[xtan-1x – log√(1 + x2)] + c
Hence, I = 2xtan-1x – log|1 + x2| + c
问题 42. ∫tan -1 (2x/(1 – x 2 ))dx
解决方案:
Given that, I = ∫tan-1(2x/(1 – x2))dx
Let us considered x = tanθ
dx = sec2θdθ
I = ∫tan-1((2tanθ)/(1 – tan2θ)) sec2θdθ
= ∫tan-1(tan2θ)sec2θdθ
= ∫2θsec2θdθ
Using integration by parts,
∫u v dx = v∫ u dx – ∫{d/dx(v) × ∫u dx}dx + c
We get
I = 2[θ∫sec2θdθ – ∫(1∫ sec2θdθ)dθ]
= 2[θtanθ – ∫tanθdθ]
= 2[θtanθ – logsecθ] + c
= 2[xtan-1x – log√(1 + x2)] + c
Hence, I = 2xtan-1x – log|1 + x2| + c
问题 43. ∫(x + 1)logxdx
解决方案:
Given that, I = ∫(x + 1)logxdx
Using integration by parts,
∫u v dx = v∫ u dx – ∫{d/dx(v) × ∫u dx}dx + c
We get
I = logx∫ (x + 1)dx – ∫(1/x ∫(x + 1)dx)dx
= (x2/2 + x)logx – ∫1/x (x2/2 + x)dx
= (x2/2 + x)logx – 1/2 ∫xdx – ∫dx
= (x + x2/2)logx – 1/2 × x2/2 – x + c
Hence, I = (x + x2/2)logx – 1/2 × x2/2 – x + c
问题 44. ∫ x 2 tan -1 xdx
解决方案:
Given that, I = ∫ x2 tan-1xdx
Using integration by parts,
∫u v dx = v∫ u dx – ∫{d/dx(v) × ∫u dx}dx + c
We get
I = tan-1x∫x2 dx – ∫(1/(1 + x2) ∫x2 dx) dx
= tan-1x(x3/3) – 1/3∫x3/(1 + x2) dx
= 1/3 x3 tan-1x – 1/3 ∫(x – x/(1 + x2))dx
= 1/3 x3 tan-1x – 1/3 × x2/2 + 1/3 ∫x/(1 + x2) dx
Hence, I = 1/3 x3tan-1x – 1/6 x2 + 1/6 log|1 + x2| + c
问题 45. ∫(e logx + sinx) cosxdx
解决方案:
Given that, I = ∫(elogx + sinx)cosxdx
= ∫(x + sinx)cosxdx
= ∫xcosxdx + ∫sinxcosxdx
= [x∫cosxdx – ∫(1]cosxdx)dx] + 1/2 ∫sin2xdx
= [xsinx – ∫ sinxdx] + 1/2 (-(cos2x)/2) + c
I = xsinx+cosx – 1/4 cos2x + c
= xsinx + cosx – 1/4 [1 – 2sin2x] + c
= xsinx + cosx – 1/4 + 1/2 sin2x + c
= xsinx + cosx – 1/4 + 1/2 sin2x + c
Hence, I = xsinx + cosx + 1/2 sin2x + d [d = c-/4]
问题 46. ∫((xtan -1 x))/(1 + x 2 ) 3/2 dx
解决方案:
Given that, I = ∫((xtan-1x))/(1 + x2)3/2dx
Let us considered tan-1x = t
1/(1 + x2) dx = dt
I = ∫(t tant)/√(1 + tan2t) dt
= ∫(t × tant)/(sect) dt
= ∫t (sint)/(cost) costdt
= ∫tsintdt
Using integration by parts,
∫u v dx = v∫ u dx – ∫{d/dx(v) × ∫u dx}dx + c
We get
I = [t]sintdt – ∫(1)sintdt)dt]
= [-tcost + ∫costdt]
= [-tcost + sint] + c
= -(tan-1x)/√(1 + x2) + x/√(1 + x2) + c
Hence, I = -(tan-1x)/√(1 + x2) + x/√(1 + x2) + c
问题 47. ∫ tan -1 (√x)dx
解决方案:
Given that, I = ∫ tan-1(√x)dx
Let us considered x = t2
dx = 2tdt
I = ∫2ttan-1tdt
Using integration by parts,
∫u v dx = v∫ u dx – ∫{d/dx(v) × ∫u dx}dx + c
We get
= 2[tan-1)t∫tdt – ∫(1/(1 + t2) ∫tdt)dt]
= 2[t2/2 tan-1t – ∫t2/2(1 + t2)dt]
= t2 tan-1t – ∫(t2 + 1 – 1)/(1 + t2)dt
= t2 tan-1t – ∫(1 – 1/(1 + t2))dt
= t2 tan-1t – t + tan-1t + c
= (t2 + 1) tan-1t – t + c
Hence, I = (x + 1)tan-1√x – √x + c
问题 48. ∫x 3 tan -1 xdx
解决方案:
Given that, I = ∫x3 tan-1xdx
= tan-1x∫x3dx – (∫(dtan-1x)/dx (∫x3 dx)dx)
= tan-1x x4/4 – (∫1/(1 + x2) (x4/4)dx)
= tan-1x x4/4 – (∫1/(1 + x2) (x4/4)dx)
= tan-1x x4/4 – (∫1/(1 + x2) (x4/4)dx)
∫ 1/(1 + x2) (x4/4)dx = 1/4 [∫1/(1 + x2) dx + (x2 – 1)dx]
∫ 1/(1 + x2) (x4/4)dx = 1/4 [tan-1x + x3/3 – x]
Hence, I = x4/4 tan-1x – 1/4 [tan-1x + x3/3 – x] + c
问题 49. ∫xsinxcos2xdx
解决方案:
Given that, I = ∫xsinxcos2xdx
= 1/2 ∫x(2sinxcos2x)dx
= 1/2 ∫x(sin(x + 2x) – sin(2x – x))dx
= 1/2 ∫x(sin3x – sinx)dx
= 1/2[x](sin3x – sinx)dx – ∫ (1)(sin3x – sinx)dx)dx]
= 1/2 [x((-cos3x)/3 + cosx) – ∫(-(cos3x)/3 + cosx)dx]
Hence, I = 1/2 [-x (cos3x)/3 + xcosx + 1/9 sin3x – sinx] + c
问题 50. ∫(tan -1 x 2 )xdx
解决方案:
Given that, I = ∫(tan-1x2)xdx
Let us considered x2 = t
2xdx = dt
I = 1/2∫tan-1tdt
= 1/2∫1tan-1tdt
= 1/2 [tan-1t∫dt – (∫1/(1 + t2)∫dt)dt]
= 1/2 [t × tan-1t – ∫t/(1 + t2) dt]
= 1/2 t × tan-1t – 1/4∫2t/(1 + t2) dt
= 1/2 t × tan-1t – 1/4 log|1 + t2| + c
Hence, I = 1/2 x2 tan-1x2 – 1/4 log|1 + x4| + c
问题 51. ∫xdx/√(1 – x 2 )
解决方案:
Given that, I = ∫xdx/√(1 – x2)
Let first function be sin-1x and second function be x/√(1 – x2).
Now, first we find the integral of the second function,
∫xdx/√(1 – x2)
Now, put t = 1 – x2
Then dt = -2xdx
Therefore,
∫ xdx/√(1 – x2) = -1/2 ∫dt/√t = -√t = -√(1 – x2)
Hence,
∫(xsin-1x)/√(1 – x2) dx
= (sin-1x)(-√(1 – x2) – ∫1/√(1 – x2) * (-√(1 – x2))dx
= -√(1 – x2) sin-1x + x + c
= x – √(1 – x2) sin-1x + c
问题 52. ∫sin 3 √x dx
解决方案:
Given that, I = ∫sin3√x dx
Let us considered √x = t
x = t2
dx = 2tdt
I = 2∫ tsin3tdt
= 2∫t((3sint – sin3t)/4)dt
= 1/2 ∫t(3sint – sin3t)dt
Using integration by parts,
∫u v dx = v∫ u dx – ∫{d/dx(v) × ∫u dx}dx + c
We get
I = 1/2 [t(-3cost + 1/3 cos3t) – ∫(-3cost + (cos3t)/3)dt]
= 1/2 [(-9tcost + tcos3t)/3 – {-3sint + (sin3t)/9}] + c
= 1/2 [(-9tcost + tcos3t)/3 + (27sint – 3sin3t)/9] + c
= 1/18[-27tcost + 3tcos3t + 27sint – 3sin3t] + c
Hence, I = 1/18[3√x cos3√x + 27sin√x – 27√x cos√x – 3sin3√x] + c
问题 53. ∫ xsin 3 xdx
解决方案:
Given that, I = ∫ xsin3xdx
= ∫x((3sinx – sin3x)/4)dx
= 1/4 ∫x(3sinx – sin3x)dx
Using integration by parts,
∫u v dx = v∫ u dx – ∫{d/dx(v) × ∫u dx}dx + c
We get
= 1/4 [x∫ (3sinx – sin3x)dx – ∫(1)(3sinx – sin3x)dx)dx]
= 1/4 [x(-3cosx + (cos3x)/3) – ∫(-3cosx + (cos3x)/3)dx]
= 1/4 [-3xcosx + (xcos3x)/3 + 3sinx – (sin3x)/9] + c
Hence, I = 1/36[3xcos3x – 27xcosx + 27sinx – sin3x] + c
问题 54. ∫cos 3 √x dx
解决方案:
Given that, I = ∫cos3√x dx
Let us considered x = t²
dx = 2tdt
= 2∫tcos3tdt
= 2∫t((3cost + cos3t)/4)dt
= 1/2 ∫t(3cost + cos3t)dt
Using integration by parts,
∫u v dx = v∫ u dx – ∫{d/dx(v) × ∫u dx}dx + c
We get
I = 1/2 [t(3sint + 1/3 sin3t) + ∫(1 × 3sint + (sin3t)/3)dt]
= 1/2 [t((9sint + sin3t)/3) + 3cost(cos3t)/9] + c
= 1/18[27tsint + 3tsin3t + 9cost + cos3t] + c
Hence, I = 1/18[27√x sin√x + 3√x sin3√x + 9cos√x + cos3√x] + c
问题 55. ∫xcos 3 xdx
解决方案:
Given that, I = ∫xcos3xdx
= ∫x((3cosx + cos3x)/4)dx
= 1/4 ∫x(3cosx + cos3x)dx
Using integration by parts,
∫u v dx = v∫ u dx – ∫{d/dx(v) × ∫u dx}dx + c
We get
I = 1/4 [x∫(3cosx + cos3x)dx – ∫(1)(3cosx + cos3x)dx)dx]
= 1/4 [x(3sinx + (sin3x)/3) – ∫ (3sinx + (sin3x)/3)dx]
= 1/4 [3xsinx + (xsin3x)/3 + 3cosx + (cos3x)/9] + c
Hence, I = (3xsinx)/4 + (xsin3x)/12 + (3cosx)/4 + (cos3x)/36 + c
问题 56. ∫tan -1 √((1 – x)/(1 + x))
解决方案:
Given that, I = ∫tan-1√((1 – x)/(1 + x))
Let us considered x = cosθ
dx = -sinθdθ
I = ∫ tan-1(tanθ/2)(-sinθ)dθ
=-1/2 ∫θsinθdθ
Let θ = u and sinθdθ = v
So that sinθ = ∫vdθ
Using integration by parts,
∫u v dx = v∫ u dx – ∫{d/dx(v) × ∫u dx}dx + c
We get
I = -1/2 (-θcosθ – ∫-cosθdθ)
= -1/2(-θcosθ + sinθ)+c
= -1/2 (-θcosθ + √(1 – cos2θ)) + c
= -1/2 (-xcos-1x + √(1 – x2)) + c
问题 57. ∫sin -1 √(x/(a + x)) dx
解决方案:
Given that, I = ∫sin-1√(x/(a + x)) dx
Let us considered x = atan2θ
dx = 2atanθsec2θdθ
I = ∫(sin-1√((atan2θ)/(a + atan2θ))(2atanθsec2θ)dθ
= ∫ (sin-1√((tan2θ)/(sec2θ)))(2atanθsec2θ)dθ
= ∫ sin-1(sinθ)(2atanθsec2θ)dθ
= ∫ 2θatanθsec2θdθ
= 2a∣θ(tanθsec2θ)dθ)
= ∫2θatanθsec2θdθ
= 2a∫θ(tanθsec2θ)dθ
= 2a[θ]tanθsec2θdθ – ∫(∫tanθsec2θdθ)dθ]
= 2a[θ (tan2θ)/2 – ∫(tan2θ)/2 dθ]
= aθtan2θ – 2a/2∫(sec2θ – 1)dθ
= aθtan2θ – atanθ + aθ + c
= a(tan-1√(x/a)) x/a – a√(x/a) + atan-1√(x/a) + c
Hence, I = xtan-1√(x/a) – √ax + atan-1√(x/a) + c
问题 58. ∫(x 3 sin -1 x²)/√(1 – x 4 ) dx
解决方案:
Given that, I = ∫(x3 sin-1x²)/√(1 – x4) dx
Let us considered sin-1x² = t
(1/√(1 – x4)(2x)dx = dt
I = ∫(x² sin-1x²)/√(1 – x4) xdx
= ∫(sint)t dt/2
= 1/2∫tsintdt
= 1/2 [t∫sintdt – ∫(1∫sintdt)dt]
= 1/2 [t(-cost)dt – ∫(1∫(-cost))dt]
= 1/2[-tcost + sint] + c
Hence, I = 1/2 [x2 – √(1 – x4) sin(-1)x2] + c
问题 59. ∫(x 2 sin -1 x)/(1 – x 2 ) 3/2 dx
解决方案:
Given that, I = ∫(x2 sin-1x)/(1 – x2)3/2dx
Let us considered sin-1x = t
(1/√(1 – x2) dx = dt
I = ∫(sin2t × t)/((1 – sin2t)) dt
= ∫(tsin2t)/(cos2t) dt
= ∫t × tan2tdt
= ∫t(sec2t – 1)dt
= ∫tsec2tdt – t2/2 + c
= t∫sec2tdt – ∫(1∫sec2tdt)dt – t2/2 + c
= t × tant – ∫tantdt – t2/2 + c
= t × tant – logsect – t2/2 + c
Hence, I = x/√(1 – x2) sin-1x + log|1 – x2| – 1/2 (sin-1x)2 + c
问题 60. ∫cos -1 (1 – x 2 / 1 + x 2 ) dx
解决方案:
Given that, I = ∫cos-1(1 – x2/ 1 + x2) dx
Let us considered, x = tant
dx = sec2tdt
I = ∫cos-1(1 – tan2t/ 1 + tan2t) sec2tdt
= ∫ 2t sec2tdt
Using integration by parts,
∫u v dx = v∫ u dx – ∫{d/dx(v) × ∫u dx}dx + c
We get
I = 2[t∫sec2tdt – ∫(1 ∫sec2tdt)dt]
= 2[t tan2t – ∫tant dt]
= 2[t tan2t – log sect] + c
= 2[x tan2x – log √1 + x2] + c
Hence, I = 2[xtan2x – log √1 + x2] + c